Addressing climate change with behavioral science: a global intervention tournament in 63 countries - Vlasceanu, M; Doell, KC; Bak-Coleman, JB; Todorova, B; Berkebile-Weinberg, MM; Grayson, SJ; Patel, Y; Goldwert, D; Pei, Y; Chakroff, A; Pronizius, E; van den Broek, KL; et al. (American Association for the Advancement of Science, 2024)
Effectively reducing climate change requires marked, global behavior change. However, it is unclear which strategies are most likely to motivate people to change their climate beliefs and behaviors. Here, we tested 11 expert-crowdsourced interventions on four climate mitigation outcomes: beliefs, policy support, information sharing intention, and an effortful tree-planting behavioral task. Across 59,440 participants from 63 countries, the interventions' effectiveness was small, largely limited to nonclimate skeptics, and differed across outcomes: Beliefs were strengthened mostly by decreasing psychological distance (by 2.3%), policy support by writing a letter to a future-generation member (2.6%), information sharing by negative emotion induction (12.1%), and no intervention increased the more effortful behavior-several interventions even reduced tree planting. Last, the effects of each intervention differed depending on people's initial climate beliefs. These findings suggest that the impact of behavioral climate interventions varies across audiences and target behaviors.